Autopsy Based Epidemiological Study Of Violent Asphyxial Deaths In Punjab (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Large proportion of medico-legal autopsies comprise of deaths due to violence. One of the major contributors to these deaths is violent deaths due to asphyxia. Objective: This study is therefore aimed to determine the frequency and epidemiology of violent asphyxial deaths autopsied in major mortuaries of Lahore and Multan, to help the process of scientific crime investigation. Material and Method: The study includes the retrospective evaluation of 119 deaths due to asphyxia out of the total number of autopsies that were conducted in the Forensic Medicine Departments of King Edward Medical University, Lahore and Nishtar Medical College, Multan over a period of two years from January 2012 to December 2013. The parameters studied were cause, manner, type of violent asphyxial death, age and gender of victim. Results: 119 out of 2016 medicolegal deaths were due to violent asphyxia with incidence rate of 5.9%. The most vulnerable age group was 21-30 years (32.7 %). Asphyxial deaths were more common in males (52.1%).Male predominance was seen in all asphyxial deaths except strangulation and traumatic asphyxia. Smothering was common in young children while throttling was seen in extremes of ages. Ligature strangulation (36.97%) and hanging (34.45%) were leading causes of violent asphyxial deaths. All smothering, ligature and manual strangulation cases (100 %) were homicidal while all traumatic asphyxia cases were accidental (100%). Majority of hanging (90.29%) cases was suicidal whereas drowning cases were predominantly accidental (75%). Conclusion: Males and young adult age group between 21–30 years are more vulnerable victims of violent asphyxial deaths. Homicidal deaths due to ligature strangulation and suicidal deaths as a result of hanging are the major causes of asphyxial deaths.
Keywords: Violent asphyxial death, autopsy, epidemiology, homicide